DEVELOPING ATTRIBUTES OF LUXURY CHAIN HOTELS IN THAILAND TO ENHANCE EXPERIENCE, DELIGHT AND TRUST FOR EXCELLENT SERVICE IN ACCOMMODATING SENIOR TRAVELERS - Tinakhat, Phisunt (RMUTT Global Business and Economics Review, 2025)
This study examines how luxury hotel chain characteristics in Thailand influence the experiences of senior tourists, with a focus on satisfaction and trust. Using structural modeling to analyze causal relationships, the research evaluates how key hotel attributes shape senior guests’ experiences in high-end accommodations. Reliability testing confirmed strong measurement scales, with Cronbach’s alpha values between 0.81 and 0.95. Data collected through an e-questionnaire from 629 senior travelers show that luxury hotel attributes significantly affect customer experience management, which in turn influences satisfaction and trust. The proposed structural equation model demonstrated an excellent fit with the empirical data, supported by strong indices: Chi-square = 183.095, df = 120, CMIN/DF = 1.526, RMSEA = 0.032, RMR = 0.007, GFI = 0.965, and TLI = 0.979. These results validate the robustness of the conceptual framework. Findings indicate that while physical facilities and service quality are essential, a holistic approach to customer experience is needed, one that integrates emotional and creative elements to meet the evolving expectations of senior guests. Effective experience management enhances satisfaction and trust, but hotels must balance emotional engagement with operational reliability to maintain credibility. Practically, the study highlights the need for luxury hotels to combine functional excellence with emotional value creation to build lasting relationships with senior travelers. Future research should explore how external factors further shape trust and loyalty.